Patterns of Reflective Solidarity and Migrant Resistance in Copenhagen and Berlin. (March 2021) - Siim, Birte; Meret, Susi
Inspired by Jodi Dean's understanding of the reflective solidarity of strangers, this contribution explores forms of migrant solidarity and resistance in Copenhagen and Berlin. It investigates how 'hybrid' forms of solidarity emerged out of different circumstances in Trampoline House and the Oranienplatz refugee protest camp. The two selected cases are particularly interesting for exploring how models of contentious and non-contentious civil society mobilisation and engagement cope with inequalities, disagreement and differences; how awareness of inequalities affects relations of solidarity between refugees and local activists as well as between groups of refugees. The analysis suggests that despite the substantial differences between the two cases, the groups involved in the research experienced similar challenges in overcoming inequalities and diversity. Arguably, the tensions and disagreements within groups can potentially develop into forms of reflective solidarity, aimed at reshaping the boundaries created by differences of race, class, ethnicity and gender.